Analisis Faktor Risiko Kejadian BBLR di RSUD Kotamobagu - Hamzah, St. Rahmawati (POLTEKKES KEMENKES MANADO, 2024)
Background: WHO estimates that globally, around 20 million LBW babies are born each year, accounting for 15.5% of all live births, and nearly 95.6% of them are born in developing countries. The trend of LBW babies in Indonesia in 2018 was 6.2%. This figure has decreased by 4% from 2013, which was 10.2%, but has not met the target of 3%. Objective: The purpose of this study was to analyze the risk of LBW incidence at RSUD Kotamobagu. Method: This study used an analytical observational design with a case-control design. The number of samples used was 88, with 44 cases and 44 controls (1:1). The sampling technique used purposive sampling that met the inclusion criteria. Data were analyzed univariately and bivariately using the chi-square test. Results: The study shows a significant relationship between parity and the incidence of LBW (p=0.012; OR=3.361), meaning that mothers with parity ≥ 3 are at 3.361 times the risk of giving birth to LBW babies compared to mothers with parity < 2. There is a significant relationship between chronic energy deficiency (CED) and the incidence of LBW (p=0.001; OR 1.157), meaning that mothers who are chronically energy deficient (CED) during pregnancy are at 1.157 times the risk of giving birth to LBW babies. Conclusion: Parity and chronic energy deficiency (CED) are risk factors for the incidence of LBW at RSUD Kotamobagu.